Pengaruh Lingkungan Pendidikan Asrama terhadap Pembentukan Nilai-nilai Karakter Mahasiswa di Asrama St.Stefanus Waena Jayapura - Sinaga, Rotua Dominika; Ema, Klarita Natalia (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2026)
This study aims to determine the influence of the boarding school environment on the formation of students' character values ​​and the extent of its influence. The method used in this study is a descriptive quantitative method with simple linear regression analysis and the coefficient of determination. The population in this study was all 24 students at the St. Stefanus Dormitory. The sample size of 24 students was based on saturated sampling, where all members of the population were sampled. Data collection techniques used were a Likert scale questionnaire, observation, interviews, and documentation. Data processing in this study used SPSS version 25. During the validity and reliability testing, 12 items of variable X were declared valid with a reliability level of 0.820, and 13 items of variable Y were declared valid with a reliability level of 0.835. The results of this study indicate a significant influence between the boarding school environment on the formation of students' character values ​​at the St. Stefanus Dormitory in Waena, Jayapura, with a 5% error rate. Given a significance value of 0.011 < 0.05, H1 is accepted and H0 is rejected. The contribution of variable X to variable Y is 22.9%, indicating a very small result, while the remaining 77.1% is influenced by other variables not yet examined in this study.